An in-situ method to estimate the tip temperature and phase selection of secondary Fe-rich intermetallics using synchrotron X-ray radiography. (May 2018) - Feng, S.; Liotti, E.; Lui, A.; Kumar, S.; Mahadevegowda, A.; O'Reilly, K.A.Q.; Grant, P.S.
Abstract: A method was developed based on synchrotron X-ray radiography to estimate tip temperatures of 203 Fe-rich intermetallic compound (IMC) particles during directional solidification of Al-Cu-Fe alloys. Tip temperatures showed two distinct IMC populations corresponding to Al6 (Fe, Cu) and Al7 Cu2 Fe, validated by post-solidification microscopy. The IMC tip undercooling of each growing IMC was estimated by comparison with its equilibrium formation temperature. The effect of Fe concentration, cooling rate and grain refiner additions on the IMC tip undercooling was studied. With a large number of IMC particles measured, we show the relationship between solidification parameters, secondary IMC selection and tip undercooling. Graphical Abstract: